A Graphene Quantum Dots–Hypochlorite Hybrid System for the Quantitative Fluorescent Determination of Total Antioxidant Capacity. Issue 30 (8th June 2017) - Wang, Min; Chen, Jie; Liu, Chenghao; Qiu, Jianding; Wang, Xiaomeng; Chen, Peng; Xu, Chenjie
Abstract : Antioxidants play a major part in the prevention and impairment of oxidative stress‐induced damages and diseases. Evaluating the antioxidants activity/capacity in food and biological fluid is proved to be useful for the diagnosis and treatment of these oxidative stress‐induced diseases. Herein, a graphene quantum dots (GQDs)–hypochlorite system to detect the antioxidants including nonenzymatic and enzymatic antioxidants in the biological fluid is proposed. The detection principle is based on the fact that antioxidants can protect the fluorescence of GQDs from hypochlorite‐caused quenching by acting as the scavengers of hypochlorite. The GQDs–hypochlorite system allows the accurate quantification of the total antioxidant capacity (TAC) of commercial drinks as well as the extracellular superoxide dismutase (SOD) secretion upon stimulation of cytokines or hyperglycemia. This system shows the excellent analytical recoveries for commercial drinks (>89.9%) and good consistency with ELISA testing for SOD secretion in cell‐conditioned medium. These results demonstrate the ability and reliability of the GQD–hypochlorite system for detecting and quantifying TAC in real drinks and complex biological fluids. Abstract : Antioxidants act as scavengers of hypochlorite and protect the fluorescence of graphene quantum dots (GQDs) from hypochlorite‐caused quenching and is described here. By monitoring the fluorescence change of GQDs–hypochlorite system in the presence of nonenzymatic or enzymatic antioxidants, total antioxidant capacity in aqueous real samples can be detected and quantified with high reliability.